Bon bagay (good stuff): A faith-based outlook on biomedical prevention among Haitians and Haitian Americans - Candice A. Sternberg; Maurice J. Chery; Maika Beauvoir; Pepita Jean; Dominique Guillaume; Joelle-Ann Joseph; Regine Thermy Jean Baptiste; Tyra Montour; Valeria Botero; Anjalie Geffrard; Chantal Napoleon; Terese Gelin; et al. (PLoS ONE, 2025)
Background Miami-Dade, Florida is a key hotspot for new HIV diagnoses. Haitians and Haitian Americans have been disproportionately affected. Churches play a critical role in information delivery in the Haitian community. This study provides an understanding of perceptions regarding Pre-exposure prophylaxis (PrEP) for HIV prevention among key informants. Methods In this qualitative study, focus groups were conducted with Haitian church leaders using snowball sampling. A semi-structured interview guide was used to engage discussions on topics including HIV prevention, PrEP, barriers to engagement in PrEP, and current services provided. Focus groups were audio recorded and transcribed. Thematic analysis was conducted on NVIVO computer software using a general inductive approach. Results Three focus groups were conducted. Twenty-seven (16 women and 11 men) individuals participated, most of whom were born in Haiti (78%) with an average age of 48. Eight key themes that emerged from the focus groups included the democratic nature of the churches, stigma, and fear regarding HIV/AIDS, lack of knowledge regarding PrEP, acknowledgment of PrEP benefits, trust, the churches’ roles as educators and culturally relevant messaging. Conclusion Churches, in partnership with trusted medical professionals and using culturally relevant messaging, are likely key strategies for increasing PrEP awareness among Haitians in Miami. Organizing health fairs and educational meetings can make churches effective platforms for PrEP awareness, leveraging their role as trusted community institutions.